2015
DOI: 10.1002/eet.1674
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Imprints on Scientific Policy Advice: Climate science–policy interactions within Austrian neo‐corporatism

Abstract: Climate policy is a prime example of the growing importance of expert advice. A plethora of advisory bodies and processes have emerged around the world to inform mitigation and adaptation policies. However, there are marked differences in the organization and practice of science-policy interactions in national contexts.Against this background, the article aims to provide an in-depth account of the imprints of the peculiar Austrian neo-corporatist culture on scientific advice in the new field of climate policy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…These divergent patterns between countries are notable in various respects: On empirical grounds, it is interesting to see that even though the expert communities of the three regions regularly exchange views and experiences, we observe convergence neither on the level of recommended policy instruments nor on the level of advisory styles. With regards to the latter, the comparative science-policy literature would have made us expect that the three regions, because they share a similar neo-corporatist policy culture, would show similar patterns of interaction between science and policy-making [42,[133][134][135]. Similarities can, for sure, be seen with regard to knowledge actors and organizational formats (see Table 1), however, not for the way scientists wriggle into politics.…”
Section: Cross-case Comparison and Discussionmentioning
confidence: 99%
“…These divergent patterns between countries are notable in various respects: On empirical grounds, it is interesting to see that even though the expert communities of the three regions regularly exchange views and experiences, we observe convergence neither on the level of recommended policy instruments nor on the level of advisory styles. With regards to the latter, the comparative science-policy literature would have made us expect that the three regions, because they share a similar neo-corporatist policy culture, would show similar patterns of interaction between science and policy-making [42,[133][134][135]. Similarities can, for sure, be seen with regard to knowledge actors and organizational formats (see Table 1), however, not for the way scientists wriggle into politics.…”
Section: Cross-case Comparison and Discussionmentioning
confidence: 99%
“…The prevalence of informal contacts entails that science-policy interactions lack transparency. (Hermann et al, 2015). Policy-makers treat scientific input as an internal concern with the effect that recommendations by committees remain invisible.…”
Section: Mind the Gap: How Research Does (Not) Inform Policymentioning
confidence: 99%
“…(Oliver et al, 2014) document an increasing amount of research stressing the serendipitous nature of the policy process which gives primacy to informal contacts. In these environments, formalized advice through contract research does not promote transparency, but shifting to research programs has boosted transparency regarding beneficiary institutions, funding amounts, topics and publication of results (Hermann et al, 2015).…”
Section: Mind the Gap: How Research Does (Not) Inform Policymentioning
confidence: 99%
See 1 more Smart Citation
“…Science can produce relevant knowledge not only about climate change and its impacts, but also about policy-making and its effectiveness. So far, climate science is brokered to policy-makers with various arrangements (Hermann et al, 2015), and social science is often concerned with monitoring and evaluating policies. Although monitoring and evaluation feedback loops can trigger policy learning (Preston et al, 2011), this has not been observed for comprehensive environmental strategies, such as those on adaptation (Steurer, 2008;Casado-Asensio and Steurer, 2014;Clar, 2019).…”
Section: Mainstreaming Climate Change Adaptation: a Literature Synthementioning
confidence: 99%